PENGARUH GREEN PRODUCT DAN GREEN PACKAGING TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP DI MALANG - Lintang Puspita Dewanti; Lina Budiarti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Public awareness of environmental preservation is increasing due to concerns that arise about health problems in the community and threaten the survival of the community and natural resources. Based on observations, The Body Shop in Malang has carried out green products and Green Packaging. This study aimed to examine the effect of green product and Green Packaging partially and simultaneously on purchasing decisions. This research was quantitative. The data collection was conducted by distributing questionnaires to 100 respondents from consumers, obtained with the purposive sampling, in Malang who made purchases and knew that The Body Shop in Malang made green products and Green Packaging. This research was administered at The Body Shop in Malang from May to June 2023. The data analysis used was multiple linear regression analysis. The results of partial hypothesis testing showed that the green product has a positive and significant effect on purchasing decisions.The Green Packaging has a positive and significant effect on purchasing decisions. The results of simultaneous hypothesis testing showed that green product and Green Packaging have a positive and significant effect on purchasing decisions. There is an influence of green product and Green Packaging on purchasing decisions of 72%, and the remaining 28% is influenced by other factors not discussed in this study. Based on the results, it can be concluded that green product and Green Packaging influence purchasing decisions of The Body Shop in Malang. The Body Shop needs to improve environmental features and optimize packaging materials